The Two Sides of YY1 in Cancer: A Friend and a Foe - Sarvagalla, Sailu; Kolapalli, Srinivasa Prasad; Vallabhapurapu, Sivakumar (Frontiers in Oncology, 2019)
Yin Yang 1 (YY1), a dual function transcription factor, is known to regulate transcriptional activation and repression of many genes associated with multiple cellular processes including cellular differentiation, DNA repair, autophagy, cell survival vs. apoptosis, and cell division. Owing to its role in processes that upon deregulation are linked to malignant transformation, YY1 has been implicated as a major driver of many cancers. While a large body of evidence supports the role of YY1 as a tumor promoter, recent reports indicated that YY1 also functions as a tumor suppressor. The mechanism by which YY1 brings out opposing outcome in tumor growth vs. suppression is not completely clear and some of the recent reports have provided significant insight into this. Likewise, the mechanism by which YY1 functions both as a transcriptional activator and repressor is not completely clear. It is likely that the proteins with which YY1 interacts might determine its function as an activator or repressor of transcription as well as its role as a tumor suppressor or promoter. Hence, a collection of YY1-protein interactions in the context of different cancers would help us gain an insight into how YY1 promotes or suppresses cancers. This review focuses on the YY1 interacting partners and its target genes in different cancer models. Finally, we discuss the possibility of therapeutically targeting the YY1 in cancers where it functions as a tumor promoter.